Digital Business: Student Entrepreneurial Interest from The Perspective of Digital Literacy and Digital Marketing: (Case Study at STIE Tuah Negeri) - N. Nasrullah; Nurul Tri Wulandari; S. Silvianti (Manunggal Halim Jaya, 2024)
This study aims to determine the effect between digital literacy and digital marketing on entrepreneurial interest. The population in this study were STIE Tuah Negeri Dumai students. This study used purposive sampling technique for sampling. The sample obtained was 95 respondents. To be able to be a sample, it must meet the predetermined criteria. Data collection in this study was conducted through a survey using a questionnaire.Data analysis conducted in this study is with statistical program for social science-SPSS. The results of this research indicate that the digital literacy variable has a significant effect on entrepreneurial interest as evidenced by the t-calculated value of 6.593 with a significance level of 0.000 < 0.5. and digital marketing variables have a significant effect on entrepreneurial interest as evidenced by the t-calculated value of 3.983 with a significance level of 0.000 < 0.5.